2008
DOI: 10.1242/jcs.027698
|View full text |Cite
|
Sign up to set email alerts
|

PKCγ mutations in spinocerebellar ataxia type 14 affect C1 domain accessibility and kinase activity leading to aberrant MAPK signaling

Abstract: Spinocerebellar ataxia type 14 (SCA14) is a neurodegenerative disorder caused by mutations in the neuronal-specific protein kinase C gamma (PKCγ) gene. Since most mutations causing SCA14 are located in the PKCγ C1B regulatory subdomain, we investigated the impact of three C1B mutations on the intracellular kinetics, protein conformation and kinase activity of PKCγ in living cells. SCA14 mutant PKCγ proteins showed enhanced phorbol-ester-induced kinetics when compared with wild-type PKCγ. The mutations led to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 65 publications
7
84
0
Order By: Relevance
“…Although neuronal PKC␥ was implicated in the proliferation of astrocytes following repeated morphine administration in vivo, the mechanism of action was not studied (46). In contrast, overexpression of PKC␥ reduced proliferation and resulted in differentiation of lens epithelial cells (47) and glioma cells (48), whereas mutations in PKC␥ reduced its kinase activity, resulting in lower ERK phosphorylation and nuclear ERK translocation, reduced MAPK signaling, and reduced survival of Purkinje cells leading to spinocerebellar ataxia-14 (49). This is the first study demonstrating that 5-HT 2B receptor-mediated proliferation is regulated by PKC␥.…”
Section: Discussionmentioning
confidence: 99%
“…Although neuronal PKC␥ was implicated in the proliferation of astrocytes following repeated morphine administration in vivo, the mechanism of action was not studied (46). In contrast, overexpression of PKC␥ reduced proliferation and resulted in differentiation of lens epithelial cells (47) and glioma cells (48), whereas mutations in PKC␥ reduced its kinase activity, resulting in lower ERK phosphorylation and nuclear ERK translocation, reduced MAPK signaling, and reduced survival of Purkinje cells leading to spinocerebellar ataxia-14 (49). This is the first study demonstrating that 5-HT 2B receptor-mediated proliferation is regulated by PKC␥.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant displays a higher fluorescence lifetime and hence a reduced FRET efficiency that fits with an open conformation. Detailed methods and statistical analysis are described elsewhere ( Verbeek et al 2008). modified with a small organic fluorophore. In the case of intracellular proteins, these molecules need to be reintroduced into the cell, usually by microinjection.…”
Section: Protein Kinase C Localizationmentioning
confidence: 99%
“…Subsequently, the translocation of both proteins was quantitatively analysed, and the translocation rates were compared. These studies revealed that the mutant PKCs have a substantially higher affinity for phorbol ester, whereas the individual (mutated) domains have less membrane affinity (Verbeek et al 2008). This approach was also used to directly compare the translocation rates of binding domains versus full-length proteins (Raghunath et al 2003).…”
Section: Protein Kinase C Localizationmentioning
confidence: 99%
See 2 more Smart Citations